GOOD GOVERNANCE OF KOPERASI WANITA SERBA USAHA “SETIA BUDI WANITA” JAWA TIMUR - Devy Sylvia Puspitasari; Unti Ludigdo (Jurnal Ilmiah Mahasiswa FEB, 2013)
This research was conducted to understand the implementation of good governance on Koperasi Wanita Serba Usaha  “Setia Budi Wanita”  Jawa Timur. Cooperative is economic organization that based on sense of family. Women’s Cooperative in the present society with the purpose to achieve the welfare of members and society with profesionalism, independent woman, qualified and integrity. This type of research  is  a  qualitative descriptive method. Instruments used in data collection are interviews, observation, and documentation.  The results of the research represent passage of the good governance principles includes of transparency  in the provisioning  information  for administrators, employees, PPL, PJ, members in a transparent and opened, so that every  employee  already  knows  how the  system  that are within  the cooperative principle  accountibility.  While,  the principle  of  responsibility  shown  SBW towards employees by providing a range of benefits, health insurance, safety and social responsibility  to the  society. Then  the principle of  independency  showed nothing intervention from the internal, but external side there is a little ideological and  philosophical  differences  cooperative.  Finally, the  Fairness  principle, shareholders (members) receive equal and fair treatment in the implementation of the RAT and the division SHU, stakeholders of the employees who were recruited based on their expertise, so the company does not discriminate against employees based on racial and establish a system of reward and punishment is fair. Key Word : Cooperative, Good Governance